Education that leaves a mark: description of field work in the town of Magueyitos, Quimixtlán - Espina Pérez, Angélica (2021)
The issue of education is a great trigger for various investigations carried out throughout the history of the human being, this has been on the rise in recent years. The interest in this topic is identified in the different scientific disciplines such as: sociology, history and philosophy to name a few; therefore, anthropology could not lag behind. The present text aims to review the field work carried out in Magueyitos-Quimixtlán in the State of Puebla, Mexico focused on education at the basic-primary level. A dense description of education in rural schools is presented; the coupling of teachers, students and tutors in the face of economic, material, technological and social difficulties that they continually face. In addition, the differences and similarities between urban and rural schools are analyzed; knowing the role of teachers and the limited access to basic services that demonstrate the absence of the State. However, the hope of parents and guardians about education as the springboard to improve the quality of life of students is observed in a theoretical and practical way.